2022
DOI: 10.56225/ijfeb.v1i4.91
|View full text |Cite
|
Sign up to set email alerts
|

Does Sharia Banking have the Capability to Increase Micro, Small and Medium Enterprises Financing?

Abstract: The contribution of Micro, Small, and Medium Enterprises (MSMEs) has played an important role in GDP and employment growth in Indonesia in the last decades, but still, MSMEs have difficulties accessing bank loans. This study examines the effect of internal factors of Islamic banking performance ratio, financing to deposit ratio, capital adequacy ratio, non-performing financing of total financing, and non-performing financing for MSMEs on the development of MSMEs financing in Islamic Banking in Indonesia. It co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Permataningayu and Mahdaria (2019) found that NPF and FDR do not directly affect the volume of financing in Islamic commercial banks, but DPK has a positive effect on financing. Yudiansyah et al (2022) highlight the importance of Islamic banking in increasing MSME financing, as MSMEs face challenges in accessing bank loans.…”
Section: Financial Performance In Islamic Banking and Msmes Financingmentioning
confidence: 99%
“…Permataningayu and Mahdaria (2019) found that NPF and FDR do not directly affect the volume of financing in Islamic commercial banks, but DPK has a positive effect on financing. Yudiansyah et al (2022) highlight the importance of Islamic banking in increasing MSME financing, as MSMEs face challenges in accessing bank loans.…”
Section: Financial Performance In Islamic Banking and Msmes Financingmentioning
confidence: 99%
“…The development of MSMEs is currently struck by many obstacles and challenges in According to various previous researchers, research conducted by Ramadhan and Official (2020) examines the influence of scientific capital on monetary execution in SMEs in the travel industry in Kambang Iwak (KI) Palembang and analysts in making oddities in research, specifically by adding several perspectives. In contrast, the research by Yudiansyah et al (2022) analyzes the ability of Islamic banking to increase MSMEs in Indonesia. This is a gap in this research.…”
Section: Introductionmentioning
confidence: 99%